Effects of Dietary Supplementation with Three Different Probiotics on Growth Performance, Antioxidant Capacity, and Intestinal Microbiota in Grass Carp (Ctenopharyngodon idella) - Wanjia Zhu; Yi Yi; Zhiwei Zou; Haipeng Li; Ting Liang; Qianhe Shi; Liwei Liu; Jianmei Su (Microorganisms)
The growing demand for sustainable aquaculture has intensified research on probiotics as antibiotic alternatives. This study aims to evaluate the effects of three probiotic supplements—1 × 1010 CFU/g of Bacillus subtilis (BS), Clostridium butyricum (CB), or Enterococcus faecalis (EF)—on growth performance, antioxidant capacity, intestinal structure, and gut microbiota in grass carp (Ctenopharyngodon idella; initial body weight: 42.52 ± 4.17 g) for 28 d. Compared to the non-supplemented (NC) control group, all probiotic-supplemented groups significantly enhanced final body weight, weight gain rate, specific growth rate, and crude protein content, and reduced feed conversion ratio (p < 0.05). Probiotic supplementation upregulated the intestinal ctrb1 gene expression and increased villus length. Serum superoxide dismutase (SOD) and catalase activity were elevated in the BS group, whereas only SOD was increased in the CB group (p < 0.05). Gut microbiota analysis revealed reduced Proteobacteria abundance in all probiotic-supplemented groups. Compared with the NC group, the BS group enriched Bacteroidetes and Prevotella_7, while the CB group promoted the abundance of Actinobacteria, Lactobacillus, and Clostridium_sensu_stricto_1. The EF group increased the abundance of Fusobacteria, Cetobacterium, and Bacteroides (p < 0.05). These findings demonstrate that dietary supplementation with probiotics enhances growth performance by modulating antioxidant responses, intestinal morphology, and microbial community balance.